Efektivitas Penerapan Metode Ular Tangga terhadap Pengetahuan dan Keaktifan Mengikuti Kelas Ibu Hamil - Lisda Widianti Longgupa; Nurfatimah Nurfatimah (Politeknik Kesehatan Tanjung Karang, 2020)
The effort to reduce maternity and child mortality is through the implementation of maternity classes. However, pregnant women who take maternity classes in Indonesia are still low because pregnant class participants feel bored with the method used. The purpose of this study was to determine the effectiveness of the application of the snake ladder method to the knowledge and activeness of taking classes in pregnant women in the Poso City Health Center. This research was carried out for 3 months. The population in this study were all trimester II and III pregnant women who examined their pregnancies. The research sample consisted of 79 people who were divided into 3 Puskesmas in the Poso City Region. The results obtained showed that the snake and ladder method lectures each showed a value of p-vaue<0,001 which means that there were differences in the mean of knowledge and activeness before and after using the snake and ladder method for pregnant women. It can be concluded that there is an increase in knowledge about pregnancy and the activeness of mothers in attending classes of pregnant women.